Sosialiasi Pemanfaatan Tanaman Herbal Sebagai Imonomodulator Untuk Meningkatan Imunitas Tubuh Masyarakat Gubeng - Siti Aminah; Mukholidah, Ainul; Salsabila, Anggun Nur; Rahman, Muhammad Fajar Wahyudi; Nihaya, Ina Uswatun; Kautsar, Achmad (Universitas Negeri Surabaya, 2023)
One of the activities that provides an overview of the usefulness of students to students community, namely through the Thematic Real Work Lecture (KKN-T). This activity a mandatory activity must be followed by all students. In this activity, members of the KKN-T 15 Surabaya group. Devoting themselves to community, especially the people of Gubeng Village, Gubeng District, Surabaya City which is a densely populated area, making a place that is prone to the spread of the virus, causing a high death rate of 1,253 people. This is one of the reasons for the lack of knowledge and understanding of the community in maintaining health to prevent and fight the Covid-19 virus. One of the efforts that must be carried out is to maintain and increase the body's resistance. Based on these problems, a solution is needed to overcome them, the Surabaya KKN-T 15 group held a socialization work program to stop Covid-19. The implementation method is in form of direct counseling by combining the lecture method with discussion. This activity aims to provide knowledge to the public about the use and manufacturing of herbal plants as immunomodulators to increase immunity and body immunity in the face of a disease.